Profile of Cholelithiasis Underwent Laparoscopic Cholecystectomy Patients at The Aloei Saboe Hospital - Romy Abdul; Safera Ariyanti; Vivien Novarina A. Kasim; Muh Nur Syukriani Yusuf; Nurliana Ibrahim (Jambura Medical and Health Science Journal, 2023)
Introduction: Cholelithiasis is one of the critical health problems. Modern lifestyles can allow gallstone disease in Indonesia to become a health problem that needs attention. The research objective is to know the profile of patients with cholelithiasis who performed laparoscopic cholecystectomy in Aloei Saboe Hospital.Method: The research design is a retrospective descriptive study. The population of this study was cholelithiasis patients who underwent laparoscopic cholecystectomy and were treated from January 2020 - December 2021, totaling 234 people. The number of samples is 86 people. We were using a purposive sampling data analysis technique, namely univariate analysis.Results: Regarding the distribution of patients based on sex, the most results were obtained from females (70 people, 81.4%), the largest age group is 46-55 years old (23 people, 26.7%), and the majority of patients did not have a history of diabetes mellitus (76 people, 88.4%).Conclusion: The distribution of cholelithiasis patients who underwent laparoscopic cholecystectomy in the Aloei Saboe Hospital is most common in women aged 46-55, and most patients have no history of diabetes mellitus. This finding may offer a primary data reference for further research adding the number of variables to determine the risk factors for cholelithiasis.